1999
DOI: 10.1590/s0100-879x1999000400002
|View full text |Cite
|
Sign up to set email alerts
|

Galectins: a key intersection between glycobiology and immunology

Abstract: Galectins are a family of evolutionarily conserved animal lectins, widely distributed from lower invertebrates to mammals. They share sequence and structure similarities in the carbohydrate recognition domain and specificity for polylactosamine-enriched glycoconjugates. In the last few years significant experimental data have been accumulated concerning their participation in different biological processes requiring carbohydrate recognition such as cell adhesion, cell growth regulation, inflammation, immunomod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 82 publications
0
16
0
1
Order By: Relevance
“…4,17 It has recently been suggested that Gal-1 triggers early upstream events in T cell physiology, such as generation of inositol-1,4,5-triphosphate and tyrosine phosphorylation of phospholipase Cg1. 31 21 These genes may act as a step in the chain of events that convert signals at the cell membrane to long-lasting responses that require gene activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,17 It has recently been suggested that Gal-1 triggers early upstream events in T cell physiology, such as generation of inositol-1,4,5-triphosphate and tyrosine phosphorylation of phospholipase Cg1. 31 21 These genes may act as a step in the chain of events that convert signals at the cell membrane to long-lasting responses that require gene activity.…”
Section: Discussionmentioning
confidence: 99%
“…4 Its presence has been localized within the central and peripheral immune compartment in thymic epithelial cells, 5 activated T cells 6,7 and activated macrophages. 8,9 It has also been found in immune privileged sites of the body such as placenta, 10,11 cornea 12 and testis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that some galectins act as immunomodulators and cell adhesion modulators (25,(27)(28)(29)(30)(31)(32)(33)(34)(35). We recently found that galectin-3 binds to L. major through L. major-specific poly-␤-galactosyl epitope (Gal␤1-3) n (16).…”
mentioning
confidence: 99%
“…Another explanation is that viral coat proteins, instead of binding to the mucosa, could be trapped by cell membrane lectins such as galectins, widely distributed in the gastrointestinal tract of mammals (34), and then be internalized. Recent studies (16) have shown that the coat proteins of CPMV, closely related to CPSMV (28), are not glycosylated.…”
Section: Discussionmentioning
confidence: 99%